Seasonal variation of peripheral blood leukocyte telomere length in Costa Rica: a population based observational study - Rehkopf, David H (2014)
OBJECTIVES: Peripheral blood leukocyte telomere length is increasingly being used as a biomarker of aging, but its natural variation in human populations is not well understood. Several other biomarkers show seasonal variation, as do several determinants of leukocyte telomere length. We examined whether there was monthly variation in leukocyte telomere length in Costa Rica, a country with strong seasonal differences in precipitation and infection. METHODS: We examined a longitudinal population based cohort of 581 Costa Rican adults age 60 and above, from which blood samples were drawn between October 2006 and July 2008. Leukocyte telomere length was assayed from these samples using the quantitative PCR method. Multivariate regression models were used to examine correlations between month of blood draw and leukocyte telomere length. RESULTS: Telomere length from peripheral blood leukocytes varied by as much as 200 base pairs depending on month of blood draw, and this difference is not likely to be due to random variation. A moderate proportion of this association is statistically accounted for by month and region specific average rainfall. We found shorter telomere length associated with greater rainfall. CONCLUSIONS: There are two possible explanations of our findings. First, there could be relatively rapid month-to-month changes in leukocyte telomere length. This conclusion would have implications for understanding the natural population dynamics of telomere length. Second, there could be seasonal differences in constituent cell populations. This conclusion would suggest that future studies of leukocyte telomere length use methods to account for the potential impact of constituent cell type.